ANÁLISE DE ESTRUTURAS PERIÓDICAS E EROSÃO NO ESPAÇO DE PARÂMETROS DE SISTEMAS NÃO-LINEARES - Santos, Vagner dos (2015)
In this work we investigated the parameter space of a system consisting of two oscillators coupled in a master-slave configuration. In order to do so we employed Lyapunov exponent's diagrams in the parameter space, the distribution of the finite-time Lyapunov exponents and its positive fraction. We were able to show that, when the slave system is coupled to the master, the shrimp-shaped periodic structures that previously existed begins to be eroded from the outside, and that the erosion progresses with the increase in the intensity of the coupling. We also showed that in the region where the erosion takes place the second Lyapunov exponent exhibits a bimodal distribution with a maximum close to zero and the other close to 0:1. By plotting the points in the phase space that belong to each maximum we were able to identify two kinds of attractors, a limit cicle and a chaotic attractor, in which the slave system intermittently moves.